2021
DOI: 10.3390/ijerph19010302
|View full text |Cite
|
Sign up to set email alerts
|

The Changes in Stress Coping, Alcohol Use, Cigarette Smoking and Physical Activity during COVID-19 Related Lockdown in Medical Students in Poland

Abstract: The ongoing COVID-19 pandemic has significantly limited social contacts, thus contributing to deepening isolation. Therefore, SARS-CoV-2 exerted on humanity not only a physical impact but also a psychological one, often increasing the feeling of stress. The long-term effects of such a state could include the management of depression, so our study aimed to analyze groups of medical students in different periods of the pandemic (at the beginning of the pandemic, after half a year of the pandemic, after one year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
23
2
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 70 publications
6
23
2
11
Order By: Relevance
“…According to the World Health Organisation, tobacco kills more than eight million people each year, including both smokers and non-smokers who are exposed to passive smoking. In our study, an increased number of people smoking cigarettes was observed, which was also confirmed by the results of studies by other authors [ 36 , 39 , 40 , 41 ]. After 6 months of the pandemic, an over two-fold increase in the number of smokers was observed, despite the fact that a part of the research group declared having quit smoking.…”
Section: Discussionsupporting
confidence: 93%
“…According to the World Health Organisation, tobacco kills more than eight million people each year, including both smokers and non-smokers who are exposed to passive smoking. In our study, an increased number of people smoking cigarettes was observed, which was also confirmed by the results of studies by other authors [ 36 , 39 , 40 , 41 ]. After 6 months of the pandemic, an over two-fold increase in the number of smokers was observed, despite the fact that a part of the research group declared having quit smoking.…”
Section: Discussionsupporting
confidence: 93%
“…In the case of stress management, positive coping has decreased. These results correspond to a study comparing the beginning of and six months into the pandemic [ 20 ]. Under the influence of the pandemic, social distancing, lockdown, and reduced social contact induce high stress in people.…”
Section: Discussionsupporting
confidence: 88%
“…There were no differences between the pre and current pandemic in smoking and high-risk drinking cases. However, some studies have reported increased smoking and drinking during the pandemic [ 20 , 21 , 22 ]. These results may differ because of the measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Kim et al [59] conducted among health college students in South Korea, and the study by Kosendiak et al [60] conducted among medical students in Poland indicate that there is a significant decrease in PA during COVID-19 pandemic and after pandemic measures have been reduced in relation to time before the beginning of the pandemic. Our study was conducted before the pandemic and future repeated research on the Western Balkan medical student population could have possible benefit because we would be able to establish if changes in PA levels were made due to changes in lifestyle of student population in past two years.…”
Section: Discussionmentioning
confidence: 99%